Endoscopic versus Microscopic Transsphenoidal Hypophysectomy: Comparison of the Endocrine Outcome – An Institutional Experience - Sumkovski, Robert; Kocevski, Ivica; Micunovic, Micun (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The transnasal transsphenoidal endoscopic approach to the sella turcica is an overwhelming alternative to the microscopic approach for the past few decades assuming into prominence as a new technique, reaching nearly gold standard for this pathology. The endoscopic approach to the pituitary has redefined accurate visualization of the sella. The panoramic view afforded by the endoscope is unparalleled as compared with the traditional conical view of the microscope. AIMS: This study aims to compare both endoscopic and microscopic technologies, including advantages and disadvantages through the results of endocrine outcome. SETTINGS AND DESIGN: Our retrospective/prospective study included 46 microscopically and 39 endoscopically treated patients during the period of 2010–2018. Tumors were classified according to the diameter and clinical outcomes were evaluated. RESULTS: Our retrospective/prospective study included 46 microscopically and 39 endoscopically treated patients during the period of 2010–2018. Tumors were classified according to the diameter, hormone activity and clinical outcomes were evaluated. Comparison results revealed more efficacious and effective endocrine control and reestablishing the endocrine homeostasis utilizing the endoscopic technique, especially in secretory active macroadenomas. Further, the extension of the resection, which was better in endoscopic approach undouptedly contributed to better endocrine control of the disease. Complication rate, including endocrine, was lower following endoscopy compared with microsurgery. CONCLUSION: This technique evidenced to have a statistically significant reduction in operative time and length of hospital stay, as well as more radical safe resection and complication control. There is also a trend toward improved endocrine outcomes and rate of return of visual defects. These two approaches are still comparable with eloquent advantages and disadvantages, formulated as balanced dialectics. In addition, the use of endoscopes, including multilocular polifilament 3D endoscope, facilitates extended approaches, reaching a delicate skull base lesions that are suprasellar, retrosellar, and parasellar, which permits visualization beyond the abilities of the microscope.